Eruption of Odontomas into the Oral Cavity: A Report of 2 Cases - Sreenivasan Bhargavan Sarojini; Ektah Khosla; Thomas Varghese; Leena Johnson Arakkal (Case Reports in Dentistry)
Odontomas are the commonest odontogenic tumors of the oral cavity and are by nature asymptomatic. They consist mainly of dental tissue that may or may not be arranged in an orderly fashion. Their presence is often detected accidentally or due to the presence of a dental disturbance such as an unerupted tooth. The very rarity of odontomas erupting into the oral cavity validates the need for more current literature on the phenomenon. Our report of two cases aims to present and discuss the rare event of an erupting odontoma with the dental community.